Physicochemical Properties of Palm Stearin and Palm Mid Fraction Obtained by Dry Fractionation - Bangun P. Nusantoro (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
Palm stearin was obtained from the 1st dry fractionation at a yield of 27.6 % with IV: 37.6 and SMP: 51.8 oC while palm mid fraction (PMF) was obtained from the 2nd dry fractionation at a yield of 24.1 % with IV: 45.8 and SMP:42.7 oC. Palm stearin consisted mainly of POP (31.06 %), PPP (20.61%) and POO (15.81 %) while palm mid fraction had disaturated TAG (such as POP: 61.05 % and POSt: 11.76 %) as the major constituents. From melting properties,palm stearin had a higher melting temperature (T : 46.7 oC) than that of PMF (T : 38.5 oC). It was also shown that,M Min general, palm stearin had higher solid fat content at any temperature compared to PMF. Palm stearin will likely besuitable as hard stock for shortenings and PMF has potency in margarine formulations.